Comparative Multimodal Meta-analysis of Structural and Functional Brain Abnormalities in Autism Spectrum Disorder and Obsessive-Compulsive Disorder - Carlisi, Christina O.; Norman, Luke J.; Lukito, Steve S.; Radua, Joaquim; Mataix-Cols, David; Rubia, Katya (Biological psychiatry (1969), 2017)
Autism spectrum disorder (ASD) and obsessive-compulsive disorder (OCD) share inhibitory control deficits possibly underlying poor control over stereotyped and repetitive and compulsive behaviors, respectively. However, it is unclear whether these symptom profiles are mediated by common or distinct neural profiles. This comparative multimodal meta-analysis assessed shared and disorder-specific neuroanatomy and neurofunction of inhibitory functions. A comparative meta-analysis of 62 voxel-based morphometry and 26 functional magnetic resonance imaging (fMRI) studies of inhibitory control was conducted comparing gray matter volume and activation abnormalities between patients with ASD (structural MRI: 911; fMRI: 188) and OCD (structural MRI: 928; fMRI: 247) and control subjects. Multimodal meta-analysis compared groups across voxel-based morphometry and fMRI. Both disorders shared reduced function and structure in the rostral and dorsomedial prefrontal cortex including the anterior cingulate. OCD patients had a disorder-specific increase in structure and function of left basal ganglia (BG) and insula relative to control subjects and ASD patients, who had reduced right BG and insula volumes versus OCD patients. In fMRI, ASD patients showed disorder-specific reduced left dorsolateral-prefrontal activation and reduced posterior cingulate deactivation, whereas OCD patients showed temporoparietal underactivation. The multimodal comparative meta-analysis shows shared and disorder-specific abnormalities. Whereas the rostrodorsomedial prefrontal cortex was smaller in structure and function in both disorders, this was concomitant with increased structure and function in BG and insula in OCD patients, but a reduction in ASD patients, presumably reflecting a disorder-specific frontostriatoinsular dysregulation in OCD in the form of poor frontal control over overactive BG, and a frontostriatoinsular maldevelopment in ASD with reduced structure and function in this network. Disorder-differential mechanisms appear to drive overlapping phenotypes of inhibitory control abnormalities in patients with ASD and OCD.